Evaluation of the radiopacity of calcium hydroxide- and glass-ionomer-based root canal sealers - Tanomaru-Filho, M. [UNESP]; Jorge, E. G. [UNESP]; Tanomaru, Juliane Maria Guerreiro [UNESP]; Gonçalves, Marcelo [UNESP] (Blackwell Publishing, 2008)
Aim To evaluate the radiopacity of calcium hydroxide-based root canal sealers (Acroseal, Sealapex and Sealer 26), a glass-ionomer-based sealer (Activ GP Sealer) and a zinc oxide and eugenol-based sealer (Intrafill).Methodology Five disc-shaped specimens (10 x 1 mm) were fabricated from each material, according to the International Organization for Standardization (ISO) 6876/2001 standard. After setting of the materials, radiographs were taken using occlusal films and a graduated aluminum step-wedge varying from 2 to 16 mm in thickness. The dental X-ray unit (GE1000) was set at 50 Kvp, 10 mA, 18 pulses s(-1) and distance of 33.5 cm. The radiographs were digitized and the radiopacity compared with that of the aluminum step-wedge, using WIXWIN-2000 software (Gendex). Data (mm Al) were submitted to ANOVA and Tukey test.Results Intrafill was the most radiopaque material (7.67 mm Al) followed by Sealer 26 (6.33 mm Al), Sealapex (6.05 mm Al) and Acroseal (4.03 mm Al). Activ GP was the least radiopaque material (1.95 mm Al, P < 0.05).Conclusions The sealers evaluated in this study had different radiopacities. However, except for the glass-ionomer-based sealer, all materials had radiopacity values above the minimum recommended by the ISO standard.
Keywords: radiology; radiopacity; root canal filling materials